Correlation Of Portal Vein Pulsatility Pattern And Severity Of Liver Disease In Patients With Cirrhosis And Portal Hypertension - Subedee, Anish; Lohani, Benu; Sharma, Shashi (Journal of Nobel Medical College, 2013)
Objective: To correlate the portal vein pulsatility pattern with severity of liver disease in patients with cirrhosis of liver and portal hypertension. Subjects and methods: Doppler signals from the main portal vein of 36 healthy adults and 52 cirrhotic patients with portal hypertension were studied. Severity of liver disease was graded using modified Child-Pugh classification. Pulsatility of portal flow was quantified using portal venous pulsatility index and complete spectral widening was defined as absence of window below the wave base. The Doppler findings were correlated between the study groups. Results: The mean pulsatility index value in control group was 0.37+0.10 and in cirrhotic patients was 0.17+0.03 (Child A- 0.21+0.02, Child B- 0.18+0.02, Child C- 0.14+0.03). The difference between control and cirrhosis group, as well as the difference within different Child classes were statistically significant (P<0.05). None of the patients in control group had complete spectral widening while 76.92% of cirrhotic patients had complete spectral widening (28.5% of Child A, 66.6% of Child B and 100% of Child C). The difference in distribution of complete spectral widening between control and cirrhotic group as well as within the cirrhotic group was statistically significant (P<0.05). Conclusion: Portal vein pulsatility index and spectral widening can reflect the early hemodynamic changes in cirrhotic patients. These changes become more pronounced with increasing severity of liver disease. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 1-8 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7664